Keberpihakan Hukum Islam Terhadap Perlindungan Anak - Nurjanah, Siti (al-'adalah, 2017)
Child protection has become an important issue in the modern world. To guarantee the future generations, children must be protected from all forms of of interference, threats, violence and exploitation carried out by adults. Protection is not only charged to parents, but also to the community, nation and state. This article tries to examine the attitude of Islam towards the issue of child protection through a search of syara arguments. Especially in the Qur'an and in the Hadith. This study finds out that Islam has a broader perspective. In guaranteeing the needs of children. The guarantees start when they are still in the wombs (fetus) to adulthood. This can be understood from the provisions of the Shari'ah which prohibits abortion and provide relief for pregnant women not to fast during the month of Ramadan. In addition, Islam also gives rights to children, such as the right to life, the right to have aqiqah (religious redemption), the right to have a good name, the right to receive breastfeeding for two years, and so on.